The compositions, characteristics, health benefits and applications of anthocyanins in Brassica crops - Li, Xinjie; Wang, Fan; Ta, Na; Huang, Jinyong (Frontiers in Plant Science, 2025)
Brassica crops, well known for their nutritional and medicinal value, encompass a diverse range of species and varieties, many of which are rich in anthocyanins. These flavonoid pigments not only contribute to the vibrant colors of Brassica plants but also possess significant antioxidant, anti-inflammatory, and neuroprotective properties. This review provides an in-depth analysis of the distribution, composition, and health benefits of anthocyanins in Brassica crops, highlighting their potential applications in the food industry and medicine. We discuss the accumulation patterns of anthocyanins in various Brassica tissues, the influence of genetic and environmental factors on their concentration, and the impact of acylation on their stability and biological activities. This review also explores the antioxidant capacity and cardioprotective effects of Brassica anthocyanins, as well as their roles in protecting against hepatic and renal injury and promoting neuroprotection. Furthermore, we examine the use of anthocyanins as natural food colorants and their integration into intelligent packaging for the real-time monitoring of food freshness. Our findings underscore the multifaceted benefits of Brassica anthocyanins, positioning them as key components in the development of functional foods and sustainable food systems.